2008
DOI: 10.1186/1476-4598-7-93
|View full text |Cite
|
Sign up to set email alerts
|

LIM only 4 is overexpressed in late stage pancreas cancer

Abstract: Background: LIM-only 4 (LMO4), a member of the LIM-only (LMO) subfamily of LIM domaincontaining transcription factors, was initially reported to have an oncogenic role in breast cancer. We hypothesized that LMO4 may be related to pancreatic carcinogenesis as it is in breast carcinogenesis. If so, this could result in a better understanding of tumorigenesis in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…A previous study showed that LMO4 is overexpressed during the differentiation of mammary epithelial cells (14), implicating it as an oncogene. Significantly, high LMO4 levels in the cell nucleus may serve as an independent predictor of mortality from breast cancer, pancreatic cancer, and tongue cancer (15)(16)(17). Our study showed that LMO4 overexpression was related to NSCLC progression and may therefore predict the prognosis of lung cancer patients, especially those with high-grade/less-differentiated NSCLC (characteristically highly proliferative).…”
Section: Discussionmentioning
confidence: 81%
“…A previous study showed that LMO4 is overexpressed during the differentiation of mammary epithelial cells (14), implicating it as an oncogene. Significantly, high LMO4 levels in the cell nucleus may serve as an independent predictor of mortality from breast cancer, pancreatic cancer, and tongue cancer (15)(16)(17). Our study showed that LMO4 overexpression was related to NSCLC progression and may therefore predict the prognosis of lung cancer patients, especially those with high-grade/less-differentiated NSCLC (characteristically highly proliferative).…”
Section: Discussionmentioning
confidence: 81%
“…LMO4 is a member of the LMO protein family, a group of four nuclear LIM Only factors (designated LMO1-4) that consist almost entirely of LIM domains (Kenny et al, 1998; Yu et al, 2008). LMO4 consist of two-tandem LIM domains connected by a small linker region and short N-terminal (22 residues) and C-terminal (25 residues) ends.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four PanIN lesions (12 PanIN-1, 11 PanIN-2, and 11 PanIN-3 lesions) and 15 samples of normal pancreatic ductal epithelial cells adjacent to PanIN lesions from patients with pancreatic ductal adenocarcinoma (n=6) or other diagnoses (IPMN or serous cystadenoma, n=9) were selectively isolated with the PALM laser microdissection platform (PALM, Carl Zeiss MicroImaging, Inc., Thornwood, NY) according to the manufacturer’s protocols (31) (Supplemental Figure 1A – D). A separate set of PanIN lesions (6 PanIN-1 lesions, 3 PanIN-2 lesions, and 2 PanIN-3 lesions) and 9 samples of normal pancreatic ductal epithelium (from patients with either pancreatic ductal adenocarcinoma (n=1) or benign neoplasms (serous cystadenoma, IPMN, n=8) were laser capture microdissected in the same fashion to validate the differential expression of candidate miRNAs.…”
Section: Methodsmentioning
confidence: 99%